Criminological perspectives on race and crime - Gabbidon, Shaun L. (Criminology and justice studies series, 2007)
A brief introduction to race, crime, and theory -- Biological perspectives on race and crime -- Sociological perspectives on race and crime -- Subcultural perspectives on race and crime -- Labeling perspectives on race and crime -- Conflict perspectives on race and crime -- Social control perspectives on race and crime -- Colonial perspectives on race and crime -- Feminist perspectives on race and crime -- Conclusion